Population Assessment and Threats to Long-Tailed Macaques (Macaca fascicularis Raffles) in Areas Outside Sumile Botanical and Zoological Park, Butuan City, Philippines - Jay Tiempo; Joshua Blancia; Kevin Canelio; Joel Mercado; Victor Corbita; Roger Sarmiento (PT FORMOSA CENDEKIA GLOBAL, 2023)
Long-tailed macaques overlap extensively with humans across their ranges in Southeast Asia and consequently live together in several locations. Human-macaque interactions were documented in the neighboring Sumile Zoological and Botanical Park in Barangay Sumile, Butuan City. Due to anthropogenic activities resulting to the loss of their natural habitat, the macaques are forced to live within human settlements resulting to a positive and negative interactions which greatly affected their population. The primary objective of this study is to assess the population of long-tailed macaques in Maibu, Butuan City. We also identified the current threats, as well as the food sources of the macaques in the area. The results showed that the current estimated population of long-tailed macaques was about 688 individuals. Based on key informant interviews, the threats to long-tailed macaque populations were attributed to mining activities, deforestation through illegal logging, and the prevalent wildlife hunting. Furthermore, researchers found that fruit trees, such as coconut, banana, papaya, mango, and root crops, such as sweet potatoes, cassava, and taro, are the main sources of food. Researchers recommend expanding the scope of future studies to include home ranges, range distances, and potential sites, to obtain a larger sample size to effectively plan conservation measures of the species.